Muscle histology and Sensory quality changes during freeze storage of North Atlantic shrimps (Pandulus borealis) - Alam, AMMN; Solberg, C; Hashem, MA (Meat Research, 2023)
It is known that inappropriate transport or storage of shrimp can adversely affect different quality parameters. An experiment was designed to store North Atlantic Shrimp at two temperatures (-20ºC & -40ºC) for 2,4,6 months and analyze the quality changes during this period from these two groups at the seafood quality laboratory of Faculty of Biosciences and Aquaculture, Bodø University College, Norway. Texture was done with TA-XT2 Texture Analyzer and Color analysis was done with Minolta Chroma meter 300, shrimp muscle histology was studied and sensory analysis was done as triangle test. During the study texture was firmer and color was whiter at -40ºC storage than at –20ºC storage. Shear force increased during freeze storage at -40ºC and decreased during storage at -20ºC. In-20ºC stored samples larger ice crystals formed between the muscles. The sensory panel found difference between the -20ºC and -40ºC stored Atlantic shrimp samples after 2 months.